“EFECTO DE EXTRACTOS VEGETALES EN Plasmopara viticola y Phakopsora euvitis EN LA Vitis labrusca, SAN MARTÍN – PERÚ” - Tello Pérez, Kerlin Javier (2014)
The research was conducted to evaluate the effect of six plant extracts in the control of downy mildew (Plasmopara viticola) and blight (Phakopsora euvitis) in the cultivation of the grapevine and to realize the economic analysis to determine the profitability. The experiment was developed in Aucaloma's locality, San Roque's district of Cumbaza, province of Lamas, department of St Martin; of latitude South 6°20'53,5", length West 76°21'21,3", altitude 850 m.s.n.m.m., zone of life Dry Tropical Forest to Humid Tropical Forest Pre Montano. The studied treatments were: Extract of Mangifera indica, Jacaranda copaia, Calycophylum spruceanum, Lonchocarpus nicou, Citrus x limonia y Averrhoa carambola. We use the design of randomized complete block with eight treatments and three replications. The evaluated variables were; of the pathogen: incident in leaves and index of intensity of hurt; of the plant: number of floral clusters, number of clusters and performance. The vegetable applied extracts, studied under ambient conditions, have not reduced the incidence of mildew, caused by Plasmopara viticola, observing increase from the first to the sixth evaluation, where it comes to 100 % of leaves affected, as well as also, they have reduced the incidence of blight in the fourth evaluation, caused by Phakopsora euvitis, in the fifth and sixth evaluation of it observes increase of the incidence, where it comes to 44 % of affected leaves. The chemical control, the extracts of A. carambola, J. copaia, and M. indica are the higher yields obtained with 1049,59; 871,04; 633,54 and 632,50 kg.ha-1 respectively unlike the others, due to the number of clusters obtained at 50 and 100 days. The results of the benefit cost analysis are not encouraging, obtaining negative results for all treatments.